230. Characterization of Antibiotic Timeout Program Strategies Across the United States. (26th November 2018) - Aljefri, Doaa; Cruce, Caroline; Kinn, Patrick; Kuper, Kristi; Schulz, Lucas T; McCreary, Erin K; Postelnick, Michael
Abstract: Background: An antibiotic timeout (ATO) provides a potential opportunity to improve antibiotic utilization and decrease inappropriate antibiotic prescribing. The CDC and Joint Commission suggest ATO as an antimicrobial stewardship program (ASP) action to support optimal antibiotic use. Unfortunately, little is known about the design and implementation of an ATO. Our primary objective was to describe different ATO models established by hospitals across the United States. Methods: Data describing ATO strategies and ASP efforts were collected via a Qualtrics survey as a part of a multicenter study conducted by Vizient™ member hospitals to research the impact of an ATO on various ASP reporting metrics. Results: Seventy-one hospitals responded to the survey. Twenty (28%) had a formalized ATO. Most institutions utilizing an ATO were community hospitals (60%) and had formalized ASPs (95%). Hospitals with an ATO program trended toward a higher average combined number of ASP physician and pharmacist FTEs than those without a formalized ATO (1.72 vs. 1.2, P = 0.28). Prescribers were responsible for the ATO in 40% of programs ( N = 8), 30% were pharmacist-led, and the remainder were multidisciplinary. ATOs were most commonly performed daily (75%) as opposed to on select days of the week and targeted patients receiving antibiotics for 72 hours. Electronic medical record (EMR)-based ATOs (where the EMR prompted the responsible personnel to respond) existed at 14 programs, whereas 4 programs performed an ATO manually through chart review. Forty percent of hospitals conducted ATO on all antibiotics and antifungals; 20% included only antibiotics in their ATO. For the remaining 40% of institutions, only select drugs were included in the ATO. Conclusion: Multiple ATO strategies are used in the United States. Most ATOs are electronic-based, performed at 72 hours of antibiotic therapy, inclusive of all antibiotics, and supported by established ASPs. To our knowledge, this is the largest descriptive study on ATO implementation in the United States. Disclosures: All authors: No reported disclosures.